ANALISIS PENGARUH AKSESIBILITAS MASYARAKAT PESISIR TERHADAP KEPUASAN LAYANAN KESEHATAN RAWAT JALAN - Roswati Roswati; Nani Yuniar; Jafriati Jafriati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Background Coastal communities really hope with the existence of health services to get proper and adequate treatment, but with access constraints that are difficult to take on the way to RSUD Kab. North Konawe. The purpose of this study was to analyze the effect of Coastal Community Accessibility on Outpatient Health Service Satisfaction at RSUD Kab. North Konawe. Methods The cross-sectional study design used Binary Logistic Regression Analysis, the number of samples was 148, the data was collected using a questionnaire. The results of this study indicate that Jalan_umum has a p-value = 0, 014> 0,05 which means that Jalan_umum has a significant effect on Health Service Centers. Then the Transportation variable has a p-value = 0.001 <0.05, which means that transportation has a significant effect on Health Service Satisfaction. While the Geographical variable has a p-value = 0.992 <0.05, which means that geography has no significant effect on Health Service Satisfaction, meaning that the geographical location of Tapunggaeya village has no impact on outpatient health service satisfaction at the North Konawe District Hospital. The conclusion in this study shows that the variables of public road facilities, transportation and geography on the satisfaction of outpatient health services at the North Konawe District Hospital simultaneously have a positive influence on the satisfaction of outpatient health services at the North Konawe District Hospital.